Bustard Sanctuary Karera : Problems and Remedies - Sharma, R. D. (Indian Forester, 1995)
Bustard Sanctuary, Karera, has no forest land. Situated inside the sanctuary are 32 revenue villages having a total human and cattle population of 33,156 and 42,907 respectively. This Bustard habitat which is also well known now for its Black-buck problem and famous Dihaila Jheel deserves proper attention to save it along with its Zizyphus rotundifolia ecosystem. The present paper highlights various problems and suggests remedial measures needed urgently to mitigate these problems. Tackling of these problems immediately is essential in order to bring Bustard Sanctuary, Karera, out of danger.